Prior Learning Assessment & Recog- nition in Canadian Universities: View from the Web - Wihak, Christine (Canadian Journal of Higher Education, 2007)
Prior Learning Assessment & Recognition (PLAR), the practice of formally assigning credit for learning gained outside the formal education system (Thomas, 2000), offers significant benefits to adult students. Previous research had demonstrated that adult students may not, however, be aware of the availability of PLAR. This study investigated the availability of PLAR information on the websites of 60 Canadian universities. The research found that 24 Canadian universities offered PLAR for advanced standing. Considerable variation existed in the ease with which PLAR information could be located and in the quality of information provided. Universities were also found to vary widely in the supports offered to learners seeking PLAR, in the formality of their institutional PLAR policies, and in the extent to which the practice is institution-wide or restricted to specific faculties or departments. Findings are discussed in terms of implications for adult learners and their advocates and for future research. RDA (Reconnaissance d’acquis), la pratique d’accorder officiellement du crédit pour un apprentissage acquis en dehors du système formel d’éducation (Thomas 2000), offre des bénéfices importants à des étudiants adultes. Des recherches faites auparavant avaient démontré que les étudiants adultes ne seraient peut-être pas au courant du RDA (Schmyr, 2003). Cette étude sur la disponibilité des informations sur RDA dans les sites web de 60 universités canadiennes a eu pour résultat de trouver que 24 universités canadiennes offraient RDA comme designation de classification scolaire avancée. La facilité avec laquelle des renseignements sur RDA pouvaient être localisés, de même que la qualité des renseignements, variaient beaucoup. L’appui offert par des universités à des étudiants recherchant RDA variait énormément, et aussi la formalité des politiques de RDA. Il s’agissait de savoir à quel point la pratique s’étendait à tous les départements d’un institut éducatif ou si elle n’était restreinte qu’à des facultés ou des départements bien spécifiques. On étudie les résultats quant aux implications pour des étudiants adultes et pour les recherches futures.